Molecular and functional study of AQY1 from Saccharomyces cerevisiae: role of the C-terminal domain - Laizé, Vincent (2014)
The yeast YPR192w gene, which encodes a protein (Aqy1p) with strong homology to aquaporins (AQPs), was cloned from nine S. cerevisiae strains. The osmotic water permeability coefficient (Pf) of X. laevis oocytes expressing the gene cloned from the S1278b strain (AQY1-1) was 5.7 times higher than the Pf of oocytes expressing the gene cloned from other strains (AQY1-2). Aqy1-1p, initially cloned without its C-terminus (Aqy1-1DCp), mediated an ;3 times higher water permeability than the full-length protein. This corresponds to a 3-fold higher protein density in the oocyte plasma membrane, as shown by freeze-fracture electron microscopy. Pf measurements in yeast spheroplasts confirmed the presence of functional water channels in S1278b and a pharmacological study indicated that this strain contains at least a second functional aquaporin.